Fretting fatigue under variable amplitude loading considering partial and gross slip regimes: Numerical analysis. (June 2020) - Pinto, A.L.; Cardoso, R.A.; Talemi, R.; Araújo, J.A.
Abstract: The main aim of this work was to numerically investigate the effect of sequences of variable amplitude shear loading on contact tractions/stresses and on the development of life estimation methodologies for these more challenging loading histories. In this setting, a finite element (FE) model has been implemented in order to simulate a cylinder on plane contact problem for an aeronautical Al 7075-T651 alloy. High-Low (H-L) and Low-High (L-H) shear amplitude loading sequences under partial and gross slip conditions were considered in three different case studies. For the case studies where gross slip was involved, the proposed life estimation procedure was enhanced to include the effect of material loss due to wear. More explicitly, such procedure was based on the use of (i) the SWT (Smith-Watson-Topper) multiaxial fatigue model, (ii) the Theory of Critical Distances, (iii) Miner's cumulative damage rule and (iv) the numerical update of the contact surfaces profiles (for loading blocks under gross slip). The numerical analyses for the case studies under partial slip revealed that, when the presence of wear is neglected in the modelling, the Miner's rule provided a divergence between the expected life for the H-L and L-H loading blocks. This difference was considerably larger when gross slip took place. For the case study involving the presence of gross slip in one of the shear loading blocks, the calculated life tended to infinite when the damage generated by the high amplitude block is greater than a certain critical value. These studies are the basis for an experimental programme which will be carried out in the 4 actuators fretting fatigue rig of the University of Brasilia. Highlights: Fretting fatigue under variable amplitude loading life assessment is carried out for Al 7075-T651. Life estimates considering and neglecting wear are compared for gross slip regime. The results showed that the sequence of loading can influence on life prediction. When considering wear for gross slip regime the damage has a plateau and life tends to infinite value.